Infectious Loss of Tissue Expanders in Breast Reconstruction: Are We Treating the Right Organisms?. Issue 2 (February 2017) - Klein, Gabriel M.; Phillips, Brett T.; Dagum, Alexander B.; Bui, Duc T.; Khan, Sami U.
Abstract : Background: Postoperative infections following tissue expander-based breast reconstruction represent a significant threat to the reconstructive process. Studies have found the incidence to be as high as 29%. There has been abundant research into the risk factors associated with these infections, although very few studies have focused on the causative organisms. The purpose of this study was to investigate the bacterial flora associated with tissue expander infections after breast reconstruction. Methods: A retrospective analysis of all patients who underwent tissue expander-based breast reconstruction at our institution between February 2010 and April 2013 was conducted. The medical records were reviewed for demographic information, medical history, operative technique, postoperative course, and culture results. Descriptive data analysis was then performed. Results: A total of 56 tissue expander infections were identified in 49 patients during the study period. 41.1% of the cultures grew gram-positive organisms, whereas 28.6% grew gram-negative species. The 2 most common organisms were Staphylococcus aureus (17.9%) and Staphylococcus epidermidis (14.3%). Pseudomonas aeruginosa was the most frequent gram-negative species and was also the third most frequent organism cultured (10.9%). Discussion: Due to the high rate of infection in breast reconstruction patients, adequate perioperative prophylaxis is necessary. The surgeon must also be prepared to treat patients who may return with infection postoperatively. Although the majority of our infections were secondary to normal skin flora, a significant proportion were caused by gram-negative species. Given these results, the empiric antibiotic of choice for postoperative infections should be reconsidered to cover for these various organisms.